2020
DOI: 10.1101/2020.04.21.053173
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Skipping a beat: heartbeat-evoked potentials reflect predictions during interoceptive-exteroceptive integration

Abstract: Several theories propose that emotions and self-awareness arise from the integration of internal and external signals and their respective precision-weighted expectations.Supporting these mechanisms, research indicates that the brain uses temporal cues from cardiac signals to predict auditory stimuli, and that these predictions and their prediction errors can be observed in the scalp heartbeat-evoked potential (HEP). We investigated the effect of precision modulations on these cross-modal predictive mechanisms… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
15
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(23 citation statements)
references
References 76 publications
5
15
3
Order By: Relevance
“…Attention is thought to increase the precision of the prediction errors of the attended sensory channel via synaptic gain control, enhancing model updating (Friston, 2009; Hohwy, 2012). Consistent with the role of attentional precision in modulating predictive mechanisms, previous research demonstrated attentional modulation of HEPs, supporting its interpretation as a precision-weighted prediction error signal (Banellis & Cruse, 2020; Mai et al, 2018; Montoya et al, 1993; Petzschner et al, 2019; Villena-González et al, 2017; Yuan et al, 2007).…”
supporting
confidence: 64%
See 4 more Smart Citations
“…Attention is thought to increase the precision of the prediction errors of the attended sensory channel via synaptic gain control, enhancing model updating (Friston, 2009; Hohwy, 2012). Consistent with the role of attentional precision in modulating predictive mechanisms, previous research demonstrated attentional modulation of HEPs, supporting its interpretation as a precision-weighted prediction error signal (Banellis & Cruse, 2020; Mai et al, 2018; Montoya et al, 1993; Petzschner et al, 2019; Villena-González et al, 2017; Yuan et al, 2007).…”
supporting
confidence: 64%
“…A final sample of 34 participants were included for both parts of subsequent EEG analyses (Median age = 20 years, Range = 18-35 years). This sample size was chosen in advance, as it provides 95% power to detect the same effect size (Cohen’s d’ = 0.58) as the within-subjects interaction between attention and cardio-audio delay observed in our previous experiment (preregistered analysis: M=0.0349, SD=0.0598; alpha=.05; note that the effect size in the final published version of that study [Banellis & Cruse., 2020] was slightly larger [0.61] due to pre-processing changes suggested by peer reviewers; GPower, (Faul et al, 2007)).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations